Revised middle Eocene - upper Oligocene calcareous nannofossil biozonation for the Southern Ocean - FIORONI, Chiara; G. Villa; D. Persico; S. W. Wise; L. Pea (2011)
Revision of the existing biostratigraphic schemes for the Southern Ocean